1997
DOI: 10.1002/bjs.1800840811
|View full text |Cite
|
Sign up to set email alerts
|

Significance of lymph node involvement at the hepatic hilum in the resection of colorectal liver metastases

Abstract: Infiltration of lymph nodes in the hepatoduodenal ligament is the most important prognostic factor following R0 resection of colorectal liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0
13

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 23 publications
2
63
0
13
Order By: Relevance
“…[22][23][24][25][26][27][28] Although hepatectomy and lymph node dissection were performed in these patients, 5-year survival was reportedly 0% to 5%. 24,25,28 Rodgers and McCall 29 reviewed 15 studies that gave survival data on node-positive patients: 145 patients received hepatic resection, and only 5 (3.4%) survived 5 years. Based on these findings together with the present results, patients with hepatic lymph node metastasis were assigned to stage 4 in the simplified staging system.…”
Section: Commentmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Although hepatectomy and lymph node dissection were performed in these patients, 5-year survival was reportedly 0% to 5%. 24,25,28 Rodgers and McCall 29 reviewed 15 studies that gave survival data on node-positive patients: 145 patients received hepatic resection, and only 5 (3.4%) survived 5 years. Based on these findings together with the present results, patients with hepatic lymph node metastasis were assigned to stage 4 in the simplified staging system.…”
Section: Commentmentioning
confidence: 99%
“…Based on these findings, the authors concluded that this sampling method is effective for determining the lymph node status of a patient. However, other authors have not found a relationship between the chains involved and the topography of the hepatic lesions (7,11,17,20) . In 1996, Elias et al (11) diagnosed microscopic lymph-node involvement in several of the lymphatic chains studied without a continuous progression from one chain to another (lymph-node-jumping metastasis).…”
Section: Introductionmentioning
confidence: 87%
“…Among those results, Kokudo et al (19) have shown that the survival rate of patients with lymph node disease who undergo curative resection and lymphadenectomy is significantly higher than that of residual-liver-disease patients without lymph-node metastases who undergo liver resection (17 months versus 8 months, P<0.05). These authors therefore suggest a possible benefit from resection and hilar lymphadenectomy in patients with lymph node involvement (7) . Two other studies have found 3-year survival rates between 38% and 45% in patients with compromised liver pedicle lymph nodes who undergo liver resection combined with lymphadenectomy.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations